2015
DOI: 10.1126/science.1259308
|View full text |Cite
|
Sign up to set email alerts
|

CENP-C reshapes and stabilizes CENP-A nucleosomes at the centromere

Abstract: Inheritance of each chromosome depends upon its centromere. A histone H3 variant, CENP-A, is essential for epigenetically marking centromere location. We find that CENP-A is quantitatively retained at the centromere upon which it is initially assembled. CENP-C binds to CENP-A nucleosomes and is a prime candidate to stabilize centromeric chromatin. Using purified components, we find that CENP-C reshapes the octameric histone core of CENP-A nucleosomes, rigidifies both surface and internal nucleosome structure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
243
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 194 publications
(257 citation statements)
references
References 56 publications
14
243
0
Order By: Relevance
“…A potential explanation for the contrast might arise from recent computational modeling experiments which suggest that CENP-A nucleosomes may be adaptable and can shear at the four helix bundles holding together the two pseudo-symmetric halves of the nucleosome 62 . This interpretation is supported, in part, by recent sm-FRET data demonstrating that CENP-A nucleosomal DNA is intrinsically flexible in vitro 63,64 , and that such flexibility is restrained in the presence of kinetochore proteins. For the left-handed canonical nucleosome, extensive studies have shown that the DNA wraps in 1.7 turns a total of 147bp of DNA with a total linking number of approximately -1.0 [45][46][47] .…”
Section: Discussionmentioning
confidence: 74%
“…A potential explanation for the contrast might arise from recent computational modeling experiments which suggest that CENP-A nucleosomes may be adaptable and can shear at the four helix bundles holding together the two pseudo-symmetric halves of the nucleosome 62 . This interpretation is supported, in part, by recent sm-FRET data demonstrating that CENP-A nucleosomal DNA is intrinsically flexible in vitro 63,64 , and that such flexibility is restrained in the presence of kinetochore proteins. For the left-handed canonical nucleosome, extensive studies have shown that the DNA wraps in 1.7 turns a total of 147bp of DNA with a total linking number of approximately -1.0 [45][46][47] .…”
Section: Discussionmentioning
confidence: 74%
“…CENP-C is a key component of most eukaryotic centromeres and links the inner and outer (microtubule binding) components of the kinetochore (Earnshaw 2015). It has been shown that CENP-C colocalizes to CENH3, thus defining active centromere chromatin (Carroll et al 2010;Kato et al 2013;Falk et al 2015). A single CENP-C candidate (RpCENP-C) was identified in an in silico analysis of the pollen mother cell transcriptome of R. pubera.…”
Section: Resultsmentioning
confidence: 99%
“…Our model can account for the recent observation that octameric CENPA nucleosomes reconstituted with 145 bp DNA from a single unit of the 12-unit DXZ1 HOR (with flanking 25-bp linkers) are stabilized by CENPC binding (Falk et al 2015). The DXZ1 dimeric cross-linked particle resembles the Cen1-like particle (which is ∼50× more abundant than DXZ1) (Fig.…”
Section: Cenpt Bridges Adjacent Cenpa Nucleosomesmentioning
confidence: 95%